Morphological Characteristics and Differentiation of Acinetobacter baumannii Colony on Selective Medium CHROMagar Acinetobacter - Wiranto, Edy; Kiranasari, Ariyani; Kusumawati, Lia; Mutiara; Tania, Tryna (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2024)
Acinetobacter is an opportunistic pathogen that causes nosocomial infections and is one of the pathogens with the highest prevalence in the world. In addition to its prevalence, the number of isolates that are resistant to antibiotics is increasing every year worldwide. Identification of these bacteria in patients is generally carried out using various methods however, each method has drawbacks such as a long time, low accuracy, and requires high costs. To overcome this, CHROMagar Acinetobacter is used and is expected to be one of the solutions for identifying Acinetobacter in patient samples due to its selectivity and accuracy. However, in this research, several non-Acinetobacter bacteria are able to grow in this media, making identification of A. baumannii using this media remain a challenge. Using phenotypic tests, 5 isolates were successfully separated from 32 A. baumannii isolates in this study (13,51%), where these 5 isolates showed the same characteristics as A. baumannii phenotypically on CHROMagar Acinetobacter results but differ in biochemical tests. Therefore, false-positive results will be obtained based solely on CHROMagar Acinetobacter results. In sum, the use of CHROMagar Acinetobacter must be followed by other conventional tests to increase the accuracy of Acinetobacter identification in specimens.